2009
DOI: 10.1038/pj.2009.316
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroalkyl end-capped oligomers possessing nonflammable and flammable characteristics in silica gel matrices after calcination at 800 °C under atmospheric conditions

Abstract: Fluoroalkyl end-capped N-(1,1-dimethyl-3-oxobutyl)acrylamide oligomer [R F -(DOBAA) n -R F ] in silica nanocomposite can exhibit a nonflammability, even after calcination at 800 1C, through the formation of ammonium hexafluorosilicate during nanocomposite reactions. In contrast, the lack of formation of ammonium hexafluorosilicate during the usual composite reactions affords a flammable behavior for the R F -(DOBAA) n -R F oligomer in silica nanocomposite. Ammonium hexafluorosilicate is formed as a result of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Especially, these fluorinated oligomers can afford the smooth dehydrofluorination of amido protons or sulfonic acid protons with fluorines in oligomers catalyzed by ammonia and silica nanoparticles to afford ammonium hexafluorosilicate during the sol-gel process [20][21][22][23][24][25][26][27][28]. The surface of these smoothly encapsulated fluorinated oligomer into silica gel nanomatrices through the effective hydrogen bonding interactions between the amido protons or sulfonic acid protons in oligomers and fluorines in ammonium hexafluorosilicate could possess an extraordinarily high oxidation resistance to exhibit a nonflammable characteristic during the calcination process at 800°C [20][21][22][23][24][25][26][27][28]. Therefore, no weight loss behavior of these ammonium-and imidazolium-type ionic liquid/silica nanocomposites would be due to the formation of ammonium hexafluorosilicate, which could be obtained by the dehydrofluorination between ammonium protons or 1-ethyl-3-methylimidazolium protons with fluorines in the corresponding counter anions catalyzed by ammonia in the presence of silica nanoparticles as a co-catalyst during the sol-gel process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially, these fluorinated oligomers can afford the smooth dehydrofluorination of amido protons or sulfonic acid protons with fluorines in oligomers catalyzed by ammonia and silica nanoparticles to afford ammonium hexafluorosilicate during the sol-gel process [20][21][22][23][24][25][26][27][28]. The surface of these smoothly encapsulated fluorinated oligomer into silica gel nanomatrices through the effective hydrogen bonding interactions between the amido protons or sulfonic acid protons in oligomers and fluorines in ammonium hexafluorosilicate could possess an extraordinarily high oxidation resistance to exhibit a nonflammable characteristic during the calcination process at 800°C [20][21][22][23][24][25][26][27][28]. Therefore, no weight loss behavior of these ammonium-and imidazolium-type ionic liquid/silica nanocomposites would be due to the formation of ammonium hexafluorosilicate, which could be obtained by the dehydrofluorination between ammonium protons or 1-ethyl-3-methylimidazolium protons with fluorines in the corresponding counter anions catalyzed by ammonia in the presence of silica nanoparticles as a co-catalyst during the sol-gel process.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, ammonium-type and imidazolium-type ionic liquids such as TEON-TFSI, TBMN-TFSI, and EMI-TFSI were able to afford no weight loss behavior toward the corresponding ionic liquid/SiO 2 nanocomposites even after calcinaton at 800°C. Previously, we reported that fluoroalkyl end-capped oligomers possessing amido protons or sulfo groups can suffer the sol-gel reactions with TEOS and silica nanoparticles in the presence of aqueous ammonia to afford the corresponding oligomer/ silica nanocomposites possessing no weight loss behavior even after calcination at 800°C [20][21][22][23][24][25][26][27][28]. Especially, these fluorinated oligomers can afford the smooth dehydrofluorination of amido protons or sulfonic acid protons with fluorines in oligomers catalyzed by ammonia and silica nanoparticles to afford ammonium hexafluorosilicate during the sol-gel process [20][21][22][23][24][25][26][27][28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S7 and S8 in the Supporting Information). Previously, we reported that encapsulated aromatic compounds possessing acidic hydroxyl groups such as BPA in fluoroalkyl end-capped acrylic acid oligomer [R F -(CH 2 CHCOOH) n -R F ; R F =CF(CF 3 )OC 3 F 7 ]/silica nanocomposite matrices can exhibit a nonflammable characteristic due to the formation of hexafluorosilicate anions in the composite matrices through the dehydrofluorination of phenoltype acidic protons and fluorines in the composites catalyzed by both ammonia and silica nanoparticles [24][25][26][27][28][29]. Therefore, encapsulated fullerene into fluorinated nanocomposite In order to clarify the presence of low molecular weight aromatic compounds in R F -(VM-SiO 2 ) n -R F /an-TiO 2 nanocomposite matrices before and after calcination, we have measured the UV-vis spectra of well-dispersed methanol solutions of R F -(VMSiO 2 ) n -R F /an-TiO 2 /BPA and/BINOL nanocomposites before and after calcination, and the results are shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…These fluorinated molecular aggregates can also interact with silica nanoparticles as a host moiety in the presence of tetraethoxysilane under alkaline conditions (aqueous ammonia) to afford the corresponding fluorinated oligomers/silica nanocomposites [R F -(M) n -R F /SiO 2 ] [3]. In these nanocomposites, fluorinated oligomers/silica nanocomposites, of whose oligomers possess the amide protons and higher acidic protons such as sulfo groups, can exhibit no weight loss behavior corresponding to the contents of oligomers even after calcination at 800°C [4][5][6]. In contrast, the fluorinated oligomers possessing no amide protons and relatively weaker acidic protons such as carboxyl groups than that of sulfo groups can afford the usual flammable characteristic Electronic supplementary material The online version of this article (doi:10.1007/s00396-016-3873-z) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 98%